Network Analysis of 500 Flights of USA Air Transportation System - Lareb Khalid; Abdul Waheed Mahesar; Bisharat Rasool Memon (University of Sindh Journal of Information and Communication Technology, 2023)
People's interest in network analysis has grown considerably in last decade. The air transportation network is considered to be a complex network, full of vitality and ramification. The main purpose of this research is to model and analyze, from a network perspective, the US air transportation network, which is one of the unique in its nature in the world. We find several features of complex network of air transportation including local and global such as degree distribution, weighted degree, clustering coefficient and betweenness and closeness centralities. The USA air transportation network has shown small-world behavior and due to non-homogenous distribution of applied network analysis metrics the network is inclined to power-law distribution.